2020
DOI: 10.1080/02699931.2020.1802231
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dysphoria on the relationship between autobiographical memories and the self

Abstract: Two experiments investigated the bi-directional relationship between episodic autobiographical memories (ABMs) and semantic self-images in dysphoric and nondysphoric individuals. Participants in Experiment 1 generated positive and negative "I am" statements, which were then used to cue specific ABMs. Nondysphoric participants generated similar numbers of ABMs to positive and negative cues, suggesting both positive and negative selfimages are supported by clusters of specific ABMs. The same was observed in dysp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Despite burgeoning research on the relationship between future thinking and the self, direct evidence for the role of future event representations in nourishing self-views is still scarce. To address this question, the present experiments investigated whether and how thinking about a personally important future event (a SDFP) modulates the content of the working self (i.e., the kind of self-conceptions that are active at a given moment), as has been demonstrated with memories for past events (Charlesworth et al, 2016;Çili & Stopa, 2015;Grace et al, 2021;Sedikides et al, 2015). With this in mind, we selected self-concept measures for which previous studies have shown consistent relationships with autobiographical memory.…”
Section: The Present Researchmentioning
confidence: 99%
“…Despite burgeoning research on the relationship between future thinking and the self, direct evidence for the role of future event representations in nourishing self-views is still scarce. To address this question, the present experiments investigated whether and how thinking about a personally important future event (a SDFP) modulates the content of the working self (i.e., the kind of self-conceptions that are active at a given moment), as has been demonstrated with memories for past events (Charlesworth et al, 2016;Çili & Stopa, 2015;Grace et al, 2021;Sedikides et al, 2015). With this in mind, we selected self-concept measures for which previous studies have shown consistent relationships with autobiographical memory.…”
Section: The Present Researchmentioning
confidence: 99%